Factors that Contribute to the Acceptance of Vasectomy as Contraception Option in East Lombok Regency - Yudi Ardiana; Pande Putu Januraga; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: The national family planning program currently promotes the role of husbands as acceptors of vasectomy as contraception. The Wanasaba Sub-district of the East Lombok Regency is one of the areas with a high number of acceptors. This phenomenon needs to be understood more deeply in order to increase vasectomy contraception uptake in other areas. This study aims to understand in depth the factors that contribute to the acceptance of vasectomy as contraception in the Sub-District of Wanasaba of East Lombok. Methods: The study used a qualitative design with phenomenology approach. The data were collected through in-depth interviews. The study was conducted among 20 participants consisting of five couples of vasectomy acceptors and five couples of non-vasectomy acceptors. Data were analyzed using thematic analysis. Results: Research showed that the decision to undergo vasectomy was voluntarily and swift without any pressure or coercion from providers or others. The main factor contributing to the acceptance of vasectomy was the availability of free, direct and fast services facilitated efficiently by providers and cadres. Another factor was economical owing to the fact that hormonal contraceptive was considered costly. The driving factor for the acceptance of vasectomy was active support from the spouse along with social acceptability of the process from the community. Conclusion: Service availability, in addition to the involvement from health workers and cadres were crucial in providing information on the procedure, and in promoting and facilitating vasectomy uptake. It is necessary to improve the capacity of cadres, family planning field workers and family planning motivators in order to increase the number of vasectomy acceptors.